CITRA GENDER PEREMPUAN-PEREMPUAN TAHANAN POLITIK INDONESIA MASA ORDE BARU DALAM NOVEL DARI DALAM KUBUR - Iswan Afandi (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2022)
The purpose of this study is to describe the image of Indonesian women political prisoners in the novel Dari Dalam Kubur. This type of research uses qualitative research with descriptive methods. The theory used in this research is the theory of feminism. The analysis focuses on the author's thoughts, social phenomena, and traditional and modern culture about women, including marginalization, stereotypes, subordination, violence, and workload. There are different types of feminism. Therefore, the type of feminism presented in the study is adjusted to the research findings. Data was collected, through library data sources, and relevant research journal articles. The data collection technique used in this research is the reading and note-taking technique. The novel is read in its entirety and then recorded things that are by the research focus. The results showed that the type of feminism used by the author of Marching was socialist-Marxist feminism. Something is interesting in the research findings, namely the phenomenon of